2022
DOI: 10.1159/000525973
|View full text |Cite
|
Sign up to set email alerts
|

Linear Low-Intensity Extracorporeal Shockwave Therapy as a Method for Penile Rehabilitation in Erectile Dysfunction Patients after Radical Prostatectomy: A Randomized, Single-Blinded, Sham-Controlled Clinical Trial

Abstract: <b><i>Introduction:</i></b> The objective of this study was to investigate the effect and feasibility of linear low-intensity extracorporeal shockwave therapy (LI-LiESWT) as a penile rehabilitation method for erectile dysfunction (ED) after bilateral nerve-sparing (NS) radical prostatectomy (RP). <b><i>Methods:</i></b> Patients who had undergone bilateral NS RP (either radical retropubic prostatectomy or robot-assisted laparoscopic RP), 3 or more months prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This suggests that despite the limited e cacy of penile rehabilitation, there is still a focus on it rather than taking a holistic approach to addressing patient sexuality. Other physiological methods of sexual rehabilitation, such as penile vibratory stimulation, stretching devices, and low-intensity extracorporeal shock wave therapy, were not utilized in our study, which is reasonable considering the limited available literature [31][32][33][34].…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that despite the limited e cacy of penile rehabilitation, there is still a focus on it rather than taking a holistic approach to addressing patient sexuality. Other physiological methods of sexual rehabilitation, such as penile vibratory stimulation, stretching devices, and low-intensity extracorporeal shock wave therapy, were not utilized in our study, which is reasonable considering the limited available literature [31][32][33][34].…”
Section: Discussionmentioning
confidence: 95%
“…Given the lack of consensus of a “best” treatment protocol, we reviewed the literature for randomized, sham-controlled trials of LiSWT for ED published in the last 10 years. Table 1 [ 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ] -summarizes the treatment protocols used, specifically distinguishing device settings, shock number, treatment sessions, and shock location (a practical variable not reported in prior LiSWT reviews). We included studies regardless of patient population, origin of ED, or concurrent medication use.…”
Section: Main Bodymentioning
confidence: 99%
“…Motil et al recently showed some promising data with early Li-ESWT intervention and combination therapy with PDE5i for penile rehabilitation ( 60 ). In this randomized, single blinded sham-controlled clinical trial, 32 patients were followed 3 months after nerve sparing RP: 16 in the treatment arm and 16 in the placebo arm (baseline IIEF-5 scores of 5.4±1.2 and 5.9±2.4, respectively).…”
Section: Restoration Of Erectile Function Following Therapy For Prost...mentioning
confidence: 99%